Papel dos traços florais na atração de abelhas da restinga - Carvalho, Emanuela Simoura (2019)
The way how flower visitors perceive the flowers is mainly related to the signs used by the flowers to attract them. In the present work, we investigate the hypothesis that the flower traits of Chamaecrista rotundifolia (Fabaceae) influence the attraction of the bees of the restinga. Data on the size and angle of flowers, intrafloral humidity and temperature and number of C. rotundifolia flowers were collected, as well as data on the frequency of visits of bees to this plant species. C. rotundifolia was visited by eight species of bees in 118 visits, and the results of the present study indicate that two characteristics of this plant species are especially related to the attraction of bees, the intrafloral temperature higher than the ambient temperature, and the reflectance pattern of their flowers. These characteristics are essential for the reproductive success of C. rotundifolia, since they help bees in the search for this species that needs vectors to reproduce.